(untitled) (Herald of the National Children’s Medical Center, 2025)
Childhood disability is one of the most pressing medico-social issues of our time. Data analysis from the Fergana region shows a steady increase in the number of children with disabilities, particularly among those under the age of three. The study aims to identify organizational and clinical-functional shortcomings in the outpatient pediatric care system, as well as to develop effective approaches for the prevention and rehabilitation of children at high neurological risk. A set of measures is proposed, including the implementation of an interdisciplinary early intervention system, the improvement of dispensary follow-up, and the introduction of individualized programs of medico-social support.